Coping with Rising Inequality in Asia : How Effective Are Fiscal Policies? - Claus, Iris; Martinez-Vazquez, Jorge; Vulovic, Violeta (MIT Press, 2014)
This paper discusses the role and effectiveness of redistributive fiscal policies and provides estimates of the effects of taxation and government expenditure on income inequality in Asia. Tax systems around the world tend to be progressive, but government expenditure is generally found to be a more effective tool for redistributing income. In Asia, government spending on social protection has a distinctive differential distributive impact. Social protection spending appears to increase income inequality in Asia, whereas it reduces it in the rest of the world. Government expenditure on housing is also adversely affecting the distribution of income in Asia. Policy options for improving the redistributional effectiveness of fiscal policies in Asia are discussed.